2022
DOI: 10.1080/23808985.2022.2142149
|View full text |Cite
|
Sign up to set email alerts
|

News recommender systems: a programmatic research review

Abstract: News recommender systems (NRS) are becoming a ubiquitous part of the digital media landscape. Particularly in the realm of political news, the adoption of NRS can significantly impact journalistic distribution, in turn affecting journalistic work practices and news consumption. Thus, NRS touch both the supply and demand of political news. In recent years, there has been a strong increase in research on NRS. Yet, the field remains dispersed across supply and demand research perspectives. Therefore, the contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 142 publications
0
2
0
Order By: Relevance
“…Previous studies have found that many users keep the recommendation feature enabled on social media platforms (Nechushtai & Lewis, 2019 ). Therefore, recommendation systems can continuously affect users’ information exposure on social media (Mitova et al, 2022 ). In reality, recommendation systems frequently push information to users based on current trending topics and their browsing history (Yang, 2016 ), which may contribute to the occurrence of vicarious traumatization (Feinstein et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that many users keep the recommendation feature enabled on social media platforms (Nechushtai & Lewis, 2019 ). Therefore, recommendation systems can continuously affect users’ information exposure on social media (Mitova et al, 2022 ). In reality, recommendation systems frequently push information to users based on current trending topics and their browsing history (Yang, 2016 ), which may contribute to the occurrence of vicarious traumatization (Feinstein et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Building on pioneering research on news recommender systems by Chesnais, Mucklo, and Sheena (1995), Kamba, Bharat, and Albers (1995), and Claypool et al (1999), Mitova et al (2023) provide a systematic survey and investigation of news recommender systems in terms of how they affect journalists/media outlets (delivery perspective) and news readers (acquisition perspective). A central challenge posed by recommender systems is the lack of diversity in the recommended items (Kunaver and Požrl 2017).…”
Section: Related Work and Research Questionsmentioning
confidence: 99%
“…We expect the interaction and transparency tool to enable "challenge-averse" individuals in the treatment group to steer the system to greater extremes than those in the control group, and enable those who are "diversity-seeking" in the treatment to steer it to less extreme and more diverse articles than those in the control. We expect mixed results for the up-vote ratio as well: the system should be able to learn user preferences better over time and hence lead to higher upvote ratios; however, some users might use the transparency and interaction tool to drastically change the system and thus experience a lower up-vote ratio than those in the control group, as providing users with more control does not guarantee its effective utilization (Mitova et al 2023).…”
Section: Research Questionsmentioning
confidence: 99%
“…Audience Attitudes about Algorithmic Technologies and AI Despite concerns regarding audience attitudes towards AI in news production, there remains a lack of concrete evidence on the subject. User attitudes towards algorithmic technologies have so far predominantly been investigated within the domain of news recommendations (Mitova et al, 2023). As Mitova et al aruge, the theoretical foundation for much of this work is the concept of the "machine heuristic" (Sundar & Kim, 2019) which posits that algorithms are perceived positively by many due to the belief that they exhibit greater neutrality and fairness compared to humans (Mitova et al, 2023, p. 92) due to their lack of human motives and emotions.…”
Section: Literature Reviewmentioning
confidence: 99%